Application of a two-part three-level model of quality control management in improving writing quality of nursing documents (全面质量管理模式下“两部三级”质量控制在提高护理文件书写质量中应用) - E Haiyan (鄂海燕); TANG Ling (唐玲); WANG Yali (王亚丽); WEI Yongchun (魏永春); DONG Yuxia (董玉霞); JIANG Jing (姜婧) (中西医结合护理)
Objective To evaluate the establishment of a two-part three-level model of quality control management in improving writing quality of nursing documents. Methods A two-part three-level model of quality control management has been carried out to improve the writing quality of nursing documents since 2016. The quality assessment outcomes of writing nursing documents in 2015-2017 were analyzed respectively. Results The score of quality assessment had increased from 97. 70 in 2015 to 98. 53 in 2016, and had continued to climb in 2017 (98. 88). Conclusion The establishment of a two-part three-level model of quality control management is effective to improve the writing quality of nursing documents. (目的 探讨科室建立并实施全面质量管理(TQC)模式下“两部三级”质量控制提高护理文件书写质量中效果。方法 2016年起, 科室开展TQC模式下“两部三级”质量控制, 细化质量控制流程, 加强环节和终末质量控制, 旨在提高护理文书书写质量。统计并比较2015、2016和2017年度科室护理文件书写考核情况。结果 护理文件书写考核评分由2015年度的97. 70分上升至2016年度的98. 53分和2017年度的98. 88分, 护理文件书写质量得到提升。结论 科室在TQC模式下建立并实施“两部三级”质量控制, 对提高护理文件书写质量具有积极意义。)